Coping strategies of displaced Ukrainian mothers - Yablonska , Tetyana; Vernik , Oleksiy; Haivoronskyi , Hlib (Insight: the psychological dimensions of society, 2025)
Modern research shows the extreme trauma of forced displacement as a result of war; the severity of PTSD, anxiety, and depression in Ukrainian displaced women. Overcoming the stress of war and displacement is considered through the prism of the concept of coherence; additional factors are depression and decision-making styles. It is substantiated that in the context of the psychological consequences of war, their comorbidity with PTSD, depression, and other disorders, and their potential impact on children, the study of mothers’ coping strategies is of particular importance. The purpose of the study is to investigate the coping strategies of Ukrainian mothers in the context of war. The sample consisted of 215 women aged 23–56 who had children. The sample was divided into three groups: 1) mothers who went abroad (n = 74); 2) internally displaced mothers (n = 77); 3) mothers who did not leave their place of residence (n = 64). Methods: a survey based on a socio-demographic questionnaire, SOC-29 scale by A. Antonovsky (1993) adapted by I. Haletska, Brief-COPE questionnaire by C. Carver (1997) adapted by T. Yablonska et al. (2023), Melbourne Decision Making Questionnaire by L. Mann et al. (1997) and Beck Depression Scale. Statistical analysis was performed using SPSS version 23 and Jamovi version 2.2.5. Descriptive statistics and frequency and correlation analyses were used. Results. It was found that most mothers, regardless of the situation of displacement, showed a sufficient level of coherence, which was manifested in more constructive coping strategies. The specifics of the measured indicators in the selected groups of mothers are characterized, and common and distinctive features are identified. In all groups, strong inverse relationships of coherence with depression and avoidance strategies were recorded, so individuals with a high level of coherence are characterized by the refusal to use unconstructive strategies and solutions, as well as lower levels of depression. In the group of mothers who went abroad, a strong inverse relationship between coherence and depression was found; these respondents are less likely to use avoidance coping, as well as procrastination and overvigilance in decision-making; they are more likely to use problem-oriented coping strategies. In the group of internally displaced mothers, there are pronounced inverse correlations of coherence with indicators of avoidance coping and non-constructive decision-making styles – avoidance, procrastination, and vigilance. In the group of mothers who did not leave their place of residence, the sense of coherence has pronounced inverse correlations with depression, avoidance coping, procrastination, and vigilance in decision-making; these mothers used emotion-focused coping to a lesser extent. Discussion and Conclusions. The specificity of the displacement situation and the sample led to differences in the identified relationships compared to other studies. The inverse correlations of a sense of coherence with the maladaptive avoidance strategy in all groups of mothers were found, which allows us to consider coherence as a trait that keeps a person from unconstructive strategies and decisions. In addition, in all groups of mothers, coherence is inversely correlated with depression, which allows it to be considered as a factor that prevents depression; accordingly, the development of a sense of coherence should be the basis of psychological assistance programs.